PENINGKATAN PRODUKTIVITAS PADI SAWAH DENGAN INTRODUKSI VARIETAS UNGGUL BARU - KARSIDI PERMADI; SUNJAYA PUTRA; OSWALD MARBUN (Agrotrop : Journal on Agriculture Science, 2011)
The increme of Wetland Rice Production with New High Yieldding Varieties The use of high yielding variety (HYV) is one of the technology components that supports rice production, besides fertilizer and irrigation. Yet the use of HYV is still slowly adopted, resulting in continuing previous varieties application. The objectives of the research were to determine the HYV with the highest yield implementing integrated crop management (ICM). The location of research was in Tanjung Sari village, Pondok salam subdistrict, Purwakarta residence in 2009 dry season. The new seven HYVs (Inpari 1, Inpari 2, Inpari 3, Inpari 4, Inpari6, Inpara 2, and Aek Sibundong) were treated with randomized complete block design (RCBD) with four replications. The results showed that Aek Sibundong variety had the highest crop height, the number of panicle per hill, and the filled grain percentage. Aek Sibundong variety had 11.7 t/ha grain yield, while that Inpari 2 had 8.26 t/ha. There were significant correlation between dry yield and the number of panicle per hill and the number of grain per panicle, with the value of 4.470 and 0.479, respectively.